2022
DOI: 10.1172/jci.insight.157612
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system immune interactome is a function of cancer lineage, tumor microenvironment, and STAT3 expression

Abstract: PCT/US2022/019436) that has generated royalty income from Celldex Therapeutics and DNAtrix; serves on the advisory boards of WCG Oncology and Caris Life Sciences; receives research support from Moleculin, Celularity, Codiak Biosciences; and received consulting fees from Novocure and Istari Oncology. AR serves as a member for Voxel Analytics and consults for Genophyll.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…One study found that high levels of traditionally “M1 markers” such as IL-6 and IL-1β were expressed by the same macrophages expressing traditionally “M2 markers” like matrix metalloproteinase (MMP)-1 and fibronectin 1 (FN1) ( 6 ). It has been shown that CD45+ myeloid cells in the GBM TME express markers of immune activation as well as immune suppression ( 42 ). A preclinical study detailed that treatment with anti-PD-1 therapy induced macrophage and microglia polarization towards a proinflammatory phenotype in glioma of CD8 -/- mice, suggesting that the therapeutic effect of PD-1 blockade may be due to innate rather than adaptive immune system function ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that high levels of traditionally “M1 markers” such as IL-6 and IL-1β were expressed by the same macrophages expressing traditionally “M2 markers” like matrix metalloproteinase (MMP)-1 and fibronectin 1 (FN1) ( 6 ). It has been shown that CD45+ myeloid cells in the GBM TME express markers of immune activation as well as immune suppression ( 42 ). A preclinical study detailed that treatment with anti-PD-1 therapy induced macrophage and microglia polarization towards a proinflammatory phenotype in glioma of CD8 -/- mice, suggesting that the therapeutic effect of PD-1 blockade may be due to innate rather than adaptive immune system function ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of using derivatives of nearest neighbour methods and cell proportion quantification for identifying clusters has been tackled also in previous literature [24, 25]. In our study, each tumor was sampled in triplicate from the centre of the tumour and the single cell data is not extracted from luminal side and advancing edge [26].…”
Section: Resultsmentioning
confidence: 99%
“…The notion of using derivatives of nearest neighbour methods and cell proportion quantification for identifying clusters has been tackled also in previous literature [24,25].…”
Section: Two Distinct Clusters Within Stage III Colorectal Cancer Tum...mentioning
confidence: 99%
“…In addition, there was no evidence of intracranial beneficial responses with lack of extracranial progression (72,73). In addition to a meaningful peripheral immune response during checkpoint blockade therapy, increased T cell numbers and cytolytic interactions with tumor cells might arbitrate successful intracranial responses following immunotherapy (43,76). PD-1 expression was also found in myeloid-derived suppressor cells, CD11b + F4/80 + macrophages, and CD11c + MHCII + dendritic cells in the tumor and the spleen of melanoma-bearing mice, albeit at different levels.…”
Section: R E V I E W S E R I S : I M M U N E E N V I R O N M E N T I ...mentioning
confidence: 99%